ESL teachers’ internet integration for hearing impairment students in a Malaysian primary school / Julinamary Parnabas, Vincent Parnabas and Antoinette Mary Parnabas - Parnabas, Julinamary; Parnabas, Vincent A.; Parnabas, Antoinette Mary (Universiti Teknologi MARA, Kedah, 2019)
English language teachers teaching hearing impairment students too are frequently pressured from various quarters to produce excellent grades both in quality and quantity in public examinations by school administrative, parents, district and state education officials as well as the Ministry of Education in Malaysia. Excellent achievements in public examinations and the massive advancement in Information Communication Technology have rapidly transformed the ESL teachers’ work culture at present. Hence, these teachers today cannot escape from the fact that many classrooms at present are technologically supported and web-connected to support the 21st century classroom teaching. Therefore, a case study was carried out to investigate the ESL teachers’ Internet integration in the classroom from a sociocultural perspective using Gee’s D/discourse theory and Social Practice theory. In this study, two ESL teachers teaching in the same hearing impairment school in northern region of Peninsula Malaysia volunteered for the semi-structure interview. They included both male and female teachers. Data were triangulated with observation and document analysis. The findings in this study confirmed that these teachers teaching in this hearing impairment school integrate the Internet for lesson preparation, classroom teaching, to fulfill the requirements from the Ministry of Education and for professional development. The findings of this study have implication for both the ESL teachers as well as teacher educators in Teachers’ Training Institutions in Malaysia.